Parents’ decision to use e-consults in preventive youth health care: A cross-sectional study on parental and nurse factors - Arina R. Brunekreeft-Budding; Ingrid I. E. Staal; Nicole R. A. Vullings; Willemieke Kroeze; Erik-Jan Smits; Gerben J. Westerhof (Journal of Child Health Care, 2026)
Using digital health interventions in prevention programs for families with young children is often optional for parents. In preventive youth health care, nurses routinely discuss availability and suitability of this option with parents. It remains unknown what drives parental decision-making and which factors influence the decision regarding use of e-consults. This study aimed to identify which nurse and parent factors are related to the parents’ decision. Data of 718 parents and 41 nurses were collected. It turned out that the option e-consult was not discussed with 206 parents. Generalized linear mixed model analyses showed that nurses with 0–3 years working experience discussed optional e-consults significantly more often with parents. Most parents (66.4%) decided to use e-consults. Parents were less likely to use e-consults when nurses had 3–6 years of working experience and a high self-reported level for ‘Collaborator’. E-consults have been in place for over 3 years, likely making them an integral part of routine care and fostering greater nurse confidence for nurses with 0–3 years of working experience. Implementation efforts should primarily focus on nurse adoption rather than parental uptake. The findings stress the value of considering the perspectives of nurses and parents when implementing person-centered digital health interventions.